THE INFLUENCE OF URBANIZATION ON TRADITIONAL FOOD PLANT KNOWLEDGE AND TRADITIONAL CUISINE OF GAYO-LUT COMMUNITY - Pangaribuan, Ivana Joy Pauline; Hidayati, Syafitri; Sunkar, Arzyana (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Traditional knowledge explains the sustainable use and management of natural resources that are critical for the long-term of ecosystems and food security one of the challenges in maintaining traditional knowledge is urbanization. This study aims to identify the diversity of food plants used by the Gayo Lut community and describe the effect of urbanization on changes in traditional knowledge. Data collection methods include freelisting and field observation. This research involved 3 groups of 16 elders, 16 non-urban, and 16 Urban. The respondents were asked to freelist by mentioning 25 of Gayo Lut traditional common food plants and interviews related to food terminology, including the food plants used. Data were analyzed with Salience Index using Anthropac, and Jaccard index to see the similarity knowledge. This study found a total 188 of food plants and 224 dishes. The effect of urbanization on food plants knowledge is significantly seen for urban community. In contrast to cuisines knowledge, urban people tend to have more knowledge, and modified recipes as a form of adaptation but still maintained distinctive flavors. This study also reveals that there is a close relationship between traditional cuisine and food plants, which can be an alternative for food plant conservation. Key words: food plant, Gayo Lut, salience index, traditional cuisine, traditional knowledge